THE ROLE OF ARTIFICIAL LIGHTING AND INTERIOR MATERIAL SELECTION IN THE COMFORT OF VISITORS TO TANATAP CAFÉ IN BEKASI - ASTRIA MELANIRA (CV KULTURA DIGITAL MEDIA, 2025)
Currently, there has been significant growth in cafes in Indonesia, highlighting the demand for variety and thematic elements. Cafes serve as social hubs for relaxation after daily routines. Enhancing visual comfort is crucial for visitor satisfaction. Artificial and natural lighting play a significant role, especially at night, adhering to established standards for optimal visual comfort. The research methodology in this study employs data collection techniques through questionnaires and observations. The sampling method used is random sampling. The results of the observations and questionnaires examined visitor comfort in artificial lighting and interior materials, with a focus on the case study of Tanatap Coffee Bekasi. Tanatap Cafe highlights its design and artificial lighting system, creating a warm and natural atmosphere with attractive interior materials, thereby enhancing visual appeal for visitors.